Organic solar cells employing electrodeposited nickel oxide nanostructures as the anode buffer layer - Yang, Hongbin (2013)
In this work, an electrodeposited nickel oxide (NiO) nanostructure used as an anode buffer layer in organic photovoltaic cells has been studied. The structure of NiO films are tailored by current density and electrodeposition time to have nano-islands or interconnecting nano-rods on indium tin oxide surface. When –CF3-modified NiO structures are used as hole transporting and electron blocking layers, the device performance is affected by the structure and electronic properties of NiO films. The best power conversion efficiency (3.05%) is achieved under an illumination of AM 1.5G (100 mW/cm2) for a device with the interconnecting nano-rods NiO buffer layer. This electrodepositing of NiO nanostructures provides an inexpensive and facile method to fabricate an efficient anode buffer for high performance photovoltaic device.